Latino STYLE: Preliminary Findings From an HIV Prevention RCT Among Latino Youth. (24th April 2020) - Lescano, Celia M; Castillo, Humberto López; Calcano, Ercilia; Mayor, Manuel; Porter, Milagro; Rivera-Torgerson, Yairí; Dion, Charles; Marhefka, Stephanie L; Barker, David; Brown, Larry K; ,
Abstract: Objective: Latino STYLE is a family-centered, HIV-focused intervention (HIV) emphasizing cultural factors and parent-adolescent communication. We hypothesized that, compared with a general health promotion (HP) intervention, the HIV arm would improve caregiver and adolescent HIV knowledge, attitudes, parental monitoring, sexual communication, and family relationships after a 3-month postintervention period. This article reports on the short-term findings of the longer trial. Methods: A single-site, two-arm, parallel, family-based, randomized, controlled trial was conducted; eligible participants were Latino adolescents aged 14–17 and their primary caregiver. The study was conducted at the University of South Florida with 227 adolescent-caregiver dyads allocated to the HIV ( n = 117) or HP ( n = 110) intervention after completing a baseline assessment. Interim measures at 3-month follow-up included demographics, HIV knowledge, self-efficacy, parental monitoring, sexual communication, family relationships, and adolescent sexual behavior. Results: Adolescents in the HIV group reported small effects in parental permissiveness and the HP group reported small effects for family support. Caregivers in both groups reported decreases in all outcomes. Incidence of past 90-day sexual intercourse decreased in both treatment arms. Among those who were sexually active over the past 90 days, the number of sex acts decreased from baseline, particularly in the HIV group. The percentage of condom-protected sex acts increased in the HIV group and decreased in the HP group, but did not reach statistical significance. Conclusions: The HIV Latino STYLE intervention was not efficacious in improving hypothesized outcomes over a 3-month period. However, exploratory analyses revealed moderate effects for decreases in adolescent sexual risk behavior, particularly in the HIV group.